Genetically Predicted Circulating Concentrations of Micronutrients and COVID-19 Susceptibility and Severity: A Mendelian Randomization Study - Daniel, Neil; Bouras, Emmanouil; Tsilidis, Konstantinos K.; Hughes, David J. (Frontiers in Nutrition, 2022)
Background Coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which since 2019 has caused over 5 million deaths to date. The pathogenicity of the virus is highly variable ranging from asymptomatic to fatal. Evidence from experimental and observational studies suggests that circulating micronutrients may affect COVID-19 outcomes. Objectives To complement and inform observational studies, we investigated the associations of genetically predicted concentrations of 12 micronutrients (β-carotene, calcium, copper, folate, iron, magnesium, phosphorus, selenium, vitamin B-6, vitamin B-12, vitamin D, and zinc) with SARS-CoV-2 infection risk and COVID-19 severity using Mendelian randomization (MR). Methods Two-sample MR was conducted using 87,870 individuals of European descent with a COVID-19 diagnosis and 2,210,804 controls from the COVID-19 host genetics initiative. Inverse variance-weighted MR analyses were performed with sensitivity analyses to assess the impact of potential violations of MR assumptions. Results Compared to the general population, nominally significant associations were noted for higher genetically predicted vitamin B-6 (Odds ratio per standard deviation [ORSD]: 1.06; 95% confidence interval [CI]: 1.00, 1.13; p-value = 0.036) and lower magnesium concentrations (ORSD: 0.33; 95%CI: 0.11, 0.96; P = 0.042) with COVID-19 infection risk. However, the association for magnesium was not consistent in some sensitivity analyses, and sensitivity analyses could not be performed for vitamin B-6 as only two genetic instruments were available. Genetically predicted levels of calcium, folate, β-carotene, copper, iron, vitamin B-12, vitamin D, selenium, phosphorus, or zinc were not associated with the outcomes from COVID-19 disease. Conclusion These results, though based only on genetically predicated circulating micronutrient concentrations, provide scant evidence for possible associations of micronutrients with COVID-19 outcomes.